Systematic Review of Suicidal Behaviors Related to Methylphenidate and Atomoxetine in Patients With Attention Deficit Hyperactivity Disorder - Kim, Jae Heon; Park, Suyeon; Lee, Yeon Jung (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2023)
This study investigated the relationship between suicidal behavior and the use of methylphenidate (MPH) or atomoxetine (ATX) in patients with attention deficit hyperactivity disorder (ADHD). The Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines were used to conduct a meta-analysis. The Physiotherapy Evidence Database scale was used to score the quality of the studies. Nine studies were included in this quantitative analysis. The analysis included 602864 patients with ADHD (521125 and 81739 patients were taking methylphenidate [MPH group] and atomoxetine [ATX group], respectively) and 19230 healthy controls. The overall estimates were in the order of the control, MPH, and ATX groups; however, no statistically significant between-group difference was observed in the incidence of events (p=0.553 for control vs. MPH; p=1.000 for control vs. ATX; p=1.000 for MPH vs. ATX). The rate of suicidal behavior was higher in the ADHD groups treated with MPH and ATX than in the control group. However, no statistically significant difference was observed between the ADHD groups treated with MPH and ATX, and the control group. Therefore, MPH and ATX did not increase suicidal behavior.